2008
DOI: 10.1016/j.neulet.2008.05.103
|View full text |Cite
|
Sign up to set email alerts
|

Heroin-induced locomotor activity and conditioned place preference in C57BL/6J and 129P3/J mice

Abstract: Differences in the locomotor stimulating and rewarding properties of drugs of abuse have been described in several inbred strains of mice, and comparisons of inbred strains with differing responses to drugs of abuse may provide crucial insight into the question of individual vulnerability to the effects of drugs of abuse. The present study was designed to examine the rewarding and locomotorstimulating effects of heroin in C57BL/6J and 129P3/J mice. Heroin produced a robust dose dependent locomotor stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 36 publications
6
28
4
Order By: Relevance
“…Mice of 129 substrains also consistently appear less responsive to the locomotor effects of cocaine (Kuzmin and Johansson, 2000; Kuzmin et al, 2000; Miner, 1997; Schlussman et al, 1998, 2003). We have reported significant strain-related differences in the locomotor stimulating and rewarding properties of heroin administration in the same mice described in the study presented here (Schlussman et al, 2008). While heroin produced dose-dependent increases in the locomotor activity of both strains of mice, C57 mice developed CPP to relatively low doses of heroin, while 129 mice developed preference only to higher doses (Schlussman et al, 2008).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Mice of 129 substrains also consistently appear less responsive to the locomotor effects of cocaine (Kuzmin and Johansson, 2000; Kuzmin et al, 2000; Miner, 1997; Schlussman et al, 1998, 2003). We have reported significant strain-related differences in the locomotor stimulating and rewarding properties of heroin administration in the same mice described in the study presented here (Schlussman et al, 2008). While heroin produced dose-dependent increases in the locomotor activity of both strains of mice, C57 mice developed CPP to relatively low doses of heroin, while 129 mice developed preference only to higher doses (Schlussman et al, 2008).…”
Section: Introductionsupporting
confidence: 64%
“…We have reported significant strain-related differences in the locomotor stimulating and rewarding properties of heroin administration in the same mice described in the study presented here (Schlussman et al, 2008). While heroin produced dose-dependent increases in the locomotor activity of both strains of mice, C57 mice developed CPP to relatively low doses of heroin, while 129 mice developed preference only to higher doses (Schlussman et al, 2008). This suggests that 129 mice are less sensitive to the rewarding effects of heroin than are C57 mice.…”
Section: Introductionsupporting
confidence: 64%
“…Heroin HCl (Sigma/Aldrich, France) was dissolved in sterile distilled water and administered subcutaneously (s.c.) in a volume of 1 ml/100 g. Doses of heroin were chosen based on previous studies in mice (Schlussman et al 2008).…”
Section: Drugsmentioning
confidence: 99%
“…There is an increasing body of evidence that opioids produce their behavioral responses in a genotype-dependent manner (Belknap et al 1993;Semenova et al 1995;Belknap et al 1998;Kest et al 2002a, b;Schlussman et al 2008). It has been shown that morphine induces locomotor activity, analgesia, and oral self-administration as well as tolerance to the morphine analgesic effects in a genotype-dependent manner in mice, with the C57Bl/6J (C57) genetic background among the most sensitive to the behavioral effects of morphine (Belknap et al 1993;Kest et al 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies focused on the rewarding properties of morphine, whereas only modest data exist concerning the effects of heroin (Szumlinski et al 2005;Schlussman et al 2008), which is the most commonly abused opiate. Moreover, although C57 mice were shown to be the most sensitive mouse strain to the rewarding properties of morphine, with contrasting effects in the DBA strain (Orsini et al 2005), the opposite effects have also been demonstrated in a conditioned place preference paradigm (Cunningham et al 1992;Semenova et al 1995).…”
Section: Introductionmentioning
confidence: 99%